Surface modification of macroporous poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate) resins for improved Candida antarctica lipase B immobilization - Miletic, Nemanja; Rohandi, Randi; Vuković, Zorica; Nastasović, Aleksandra; Loos, Katja (Reactive and Functional Polymers, 2009)
Crosslinked macroporous hydrophilic poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate) [abbreviated poly(GMA-co-EGDMA)] with identical chemical structure (60% of glycidyl methacrylate) but with varied average pore sizes (from 30 to 560 nm), specific surface areas (from 13.2 to 106.0 m2/g), specific volumes (from 0.755 to 1.191 cm3/g) and particle sizes (<100 lm–630 lm) were synthesized via suspension polymerization. Modifications of poly(GMA-co-EGDMA) with various diamines (1,2-diaminoethane, 1,4-diaminobutane, 1,6-diaminohexane and 1,8-diaminooctane), 2-fluoroethylamine, glutaraldehyde and cyanuric chloride were carried out. The influence of the interaction between Candida antarctica lipase B (Cal-B) and various carriers during immobilization on the loading and hydrolytic activity (hydrolysis of para-nitrophenyl acetate) of the immobilized Cal-B were studied. Immobilization of Cal-B was performed at different temperatures and pH values. Cal-B immobilized at 30 C and pH 6.8 was leading to increased activities. Purely physical adsorption between enzyme and copolymer was observed on carriers in which amine or fluorine groups were introduced into the carrier structure by modification with various diamines or 2-fluoroethylamine. As a consequence enzyme loading and activity decreases. In contrary, modification of the poly(GMA-co-EGDMA) with glutaraldehyde and cyanuric chloride results in a covalent connection between enzyme and carrier. The obtained results show a significant increase in Cal-B activity. The influence of the amount of glutaraldehyde and cyanuric chloride used for modification was screened. Increasing the amount of glutaraldehyde or cyanuric chloride used for modification resulted in an increase of the enzyme loading. Consequently, higher amount of glutaraldehyde used led to a higher fraction of the enzyme molecules that are covalently connected on to the carrier. As the amount of glutaraldehyde or cyanuric chloride used for modifications increases, activity of immobilized C. antarctica ...